Metabolic dysfunction, rather than obesity, is a risk factor for chronic kidney disease in Chinese population - Shan Yang; Jiaxiu Ling; Siliang Zhang; Yang Li; Gangyi Yang (The Aging Male)
Background Metabolic dysfunction and obesity are closely related to chronic kidney disease (CKD). However, studies on the relationship between various metabolic syndrome-body mass index (MetS-BMI) phenotypes and the risk of CKD in the Chinese population have not yet been explored.Materials and methods Data from the China Health and Retirement Longitudinal Study (CHARLS) 2015 were analyzed in this study. This study enrolled 12,054 participants. Participants were divided into six distinct groups according to their MetS-BMI status. Across the different MetS-BMI groups, the odd ratios (ORs) for CKD were determined using multivariable logistic regression models.Results The prevalence of CKD was higher in metabolically unhealthy groups than in the corresponding healthy groups. Moreover, the fully adjusted model showed that all metabolically unhealthy individuals had an increased risk of developing CKD compared to the metabolically healthy normal weight group (OR = 1.62, p = 0.002 for the metabolically unhealthy normal weight group; OR = 1.55, p < 0.001 for the metabolically unhealthy overweight group; and OR = 1.77, p < 0.001 for the metabolically unhealthy obesity group.Conclusions This study is the first to evaluate the relationship between the MetS-BMI phenotype and renal prognosis in the Chinese population. Individuals with normal weights are at different risk of developing CKD depending on their different metabolic phenotypes.